bao quynh Cao
6 tháng 8 2016 lúc 9:27

p=ab(a-b)+bc(b-c)+ca(c-a)

p=ab(a-b)+b^2c-bc^2+ac^2-a^2c

p=ab(a-b)+(ac^2-bc^2)+(a^2c-b^2c)

p=ab(a-b)+c^2(a-b)+c(a^2-b^2)

p=ab(a-b)+c^2(a-b)+C(a+b)(a-b)

p=(a-b)(ab+c^2+ac+bc)

Bình luận (0)
phạm văn tuấn
14 tháng 1 2018 lúc 10:44

p=ab(a-b)+bc(b-c)+ca(c-a)

p=ab(a-b)+b^2c-bc^2+ac^2-a^2c

p=ab(a-b)+(ac^2-bc^2)+(a^2c-b^2c)

p=ab(a-b)+c^2(a-b)+c(a^2-b^2)

p=ab(a-b)+c^2(a-b)+C(a+b)(a-b)

p=(a-b)(ab+c^2+ac+bc)

Bình luận (0)

Các câu hỏi tương tự

Khoá học trên OLM của Đại học Sư phạm HN

Loading...

Khoá học trên OLM của Đại học Sư phạm HN